ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU WAJIB PAJAK TERHADAP PENGGUNAAN E-FILING (Studi Pada Wajib Pajak Orang Pribadi Di KPP Pratama Semarang Timur) - Atikasari Wahyu Wardhani, 13.05.52.0121; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This research aims to investigate the factors that influenced the behavioral taxpayers for using e-filing. Dependent variable is use in this reasearch is using e-Filing, while independent variables are perceived usefulness, perceived ease of use, security and privacy, readiness technology taxpayers informastion, the satisfaction of the taxprayer. The data used in this study are primary data using questionnaires media. This study was conducted on individual taxprayers who use e-Filing with the number of respondents as many as 103 people and listed on KPP Pratama Semarang Timur. The sampling technique taking was convenience sampling. The data analysis technique used was doubled regression analysis test by using SPSS program. The results of this research showed that Perceive Ease of Use,Readiness Technology Taxpayers Informastion and The Satisfaction of the Taxprayer significant effect on the use of e-Filing. Perceived Usefulness, and Security and Privacy does not significantly influence the use of e-Filing.Keywords: e-Filing, Perceived Usefulness, Perceived Ease of Use, Security and Privacy, Readiness Technology Taxpayers Informastion, The Satisfaction of the Taxprayer